All inorganic mixed halide perovskite nanocrystal-graphene hybrid photodetector : from ultrahigh gain to photostability - Surendran, Abhijith (2020)
Hybrid graphene-perovskite photodetectors embrace the excellent photoabsorption properties of perovskites and high carrier mobility of graphene in a single device. Here, we demonstrate the integration of halide-ion-exchanged CsPbBr x I3-x nanocrystals (NCs) as a photoabsorber and graphene as a transport layer. The NCs conform to a cubic lattice structure and exhibit an optical band gap of 1.93 eV. The hybrid device attained a maximum responsivity of 1.13 × 104 A/W and specific detectivity of 1.17 × 1011 Jones in low light intensity (∼80 μW/cm2). Specifically, an ultrahigh photoconductive gain of 9.32 × 1010 is attained because of fast hole transit time in the graphene transistor and long recombination lifetime in the perovskite NCs simultaneously. The phototransistor also shows good stability and can maintain ∼95% of the photocurrent under continuous illumination over 5 h and ∼82% under periodic illumination over 37 h. Our results also revealed that the common issue of ion separation and segregated halide domains in mixed halide perovskite NCs do not occur under low light intensities. The intensive degradation of CsPbBr x I3-x NCs is only observed under stronger light excitation (≥55 mW/cm2), reflecting as emission shifts. Our work establishes the use of fully inorganic perovskite NCs as highly stable photodetectors with high responsivity and low power light detection.